Cross Sectional Evaluation of Pre-operative Predictive Factors for Difficult Laparoscopic Cholecystectomy - Haseeb; Shaheer Hassan; Abdullah Ayub; Mian Afaq Ali; Muhammad Javed Shakir; Muhammad Shahid Farooq (Pakistan Journal of Medicine and Dentistry)
Background: Laparoscopic gallbladder removals are performed in several cases, though complications can necessitate the conversion to open surgery. The identification of risk factors for difficult laparoscopic cholecystectomy (LC) enhances surgical planning and patient safety. The objective of the study was to evaluate the demographic, clinical, and imaging parameters in patients with cholecystitis that may predict the difficulty of LC.